Integrated management of seed and soil borne diseases of safflower by seed treatment - V.B. Akashe; V.M. Amrutsagar, D.V. Indi*, D.R. Murumkar, S.K. Shinde (Indian Phytopathology, 2016)
A field experiment was conducted for 4 rabi seasons from 2011-12 to 2014-15 to evaluate the efficacy of different fungicides and bioagents as seed dressers for management of seed and soil borne diseases of safflower. Cymoxanil 8% + mancozeb 64% (0.2%) recorded the least intensity of Alternaria leaf spot (15.54%), Fusarium wilt (7.48%) and Phytophthora seedling blight (10.53%). Carbendazim 12% + mancozeb 63% 0.2%, metalaxyl 8% + mancozeb 64% 0.2%, tebuconazole 0.2% and Trichoderma harzianum Th4d SC @ 2 ml/kg seed were next effective against Alternaria leaf spot and Fusarium wilt while metalaxyl 8% + mancozeb 64% 0.2% and captan 50 WP 0.3% were next effective against Phytophthora blight. Seed treatment with cymoxanil + mancozeb recorded the highest seed yield (921 kg/ha) followed by carbendazim + mancozeb (722 kg/ha), captan (702 kg/ha) and Trichoderma harzianum (701 kg/ha). Cymoxanil + mancozeb recorded the highest B:C ratio of 2.14 followed by carbendazim + mancozeb (1.68), Trichoderma harzianum (1.63) and captan (1.63).